Histological hallmarks and role of Slug/PIP axis in pulmonary hypertension secondary to pulmonary fibrosis. Issue 9 (29th August 2019) - Ruffenach, Gregoire; Umar, Soban; Vaillancourt, Mylene; Hong, Jason; Cao, Nancy; Sarji, Shervin; Moazeni, Shayan; Cunningham, Christine M; Ardehali, Abbas; Reddy, Srinivasa T; Saggar, Rajan; Fishbein, Gregory; et al.
Abstract: Pulmonary hypertension secondary to pulmonary fibrosis (PF‐PH) is one of the most common causes of PH, and there is no approved therapy. The molecular signature of PF‐PH and underlying mechanism of why pulmonary hypertension (PH) develops in PF patients remains understudied and poorly understood. We observed significantly increased vascular wall thickness in both fibrotic and non‐fibrotic areas of PF‐PH patient lungs compared to PF patients. The increased vascular wall thickness in PF‐PH patients is concomitant with a significantly increased expression of the transcription factor Slug within the macrophages and its target prolactin‐induced protein (PIP), an extracellular matrix protein that induces pulmonary arterial smooth muscle cell proliferation. We developed a novel translational rat model of combined PF‐PH that is reproducible and shares similar histological features (fibrosis, pulmonary vascular remodeling) and molecular features (Slug and PIP upregulation) with human PF‐PH. We found Slug inhibition decreases PH severity in our animal model of PF‐PH. Our study highlights the role of Slug/PIP axis in PF‐PH. Synopsis: Pulmonary hypertension (PH) is a major complication of pulmonary fibrosis (PF), yet it is poorly understood. This study highlights the Slug/PIP axis as a key driver of vascular remodeling in pulmonary hypertension secondary to pulmonary fibrosis (PF‐PH) patients. Vascular walls were thickened in both fibrotic and non‐fibrotic areas in the lungs of PF‐PH patients, but wall thickening was mainly restricted to fibrotic areas of PF patients. In PF‐PH patients, the transcriptional factor Slug was up‐regulated in macrophages and led to increased vascular wall thickness through its target PIP. Inhibition of Slug ameliorated PH in an animal model that recapitulates human histological and molecular characteristics of PF‐PH. Abstract : Pulmonary hypertension (PH) is a major complication of pulmonary fibrosis (PF), yet it is poorly understood. This study highlights the Slug/PIP axis as a key driver of vascular remodeling in pulmonary hypertension secondary to pulmonary fibrosis (PF‐PH) patients.